Infant autonomic functioning and neonatal abstinence syndrome - Jansson, Lauren M. (2010)
BACKGROUND: Neonatal abstinence syndrome (NAS) expression is widely variable among affected infants and the reasons for this variability are largely unknown; mechanisms that predispose infants to NAS expression are not understood. It has been postulated that the regulatory problems of prenatally drug exposed infants are manifested in dysfunctional vagal regulation of autonomic processes. The current study examines whether cardiac vagal tone, an indicator of parasympathetic neuroregulation, provides a marker for autonomic dysregulation subsequently expressed as NAS in prenatally opioid-exposed newborns. METHODS: Heart period (HP) and cardiac vagal tone (V) were derived from electrocardiogram data collected from 64 methadone-exposed infants on postnatal days 1 and 3. The postpartum NAS course was assessed serially. RESULTS: Infants with lower V on day 1 had significantly higher NAS symptomatology on day 3. Boys had more severe NAS symptoms than girls through the first 4 days of life and, among infants receiving pharmacologic treatment for NAS, boys required longer treatment course and hospitalizations. Greater poly-drug exposure, detected through toxicology screening throughout pregnancy, and cocaine use in particular, were associated with lower V and shorter HP (faster heart rate) in newborns. Multiple regression models accounted for 25 to 35% of the variance in NAS symptoms and duration of hospitalization in methadone-exposed infants. Significant predictors included infant sex, SSRI/SNRI use, and cigarette smoking. CONCLUSIONS: Results support the hypothesis of a biologic vulnerability of autonomic regulatory functioning in methadone-exposed infants and greater male infant vulnerability to maternal methadone use.